Exposure to hazardous air pollutants and the risk of amyotrophic lateral sclerosis. (February 2015) - Malek, Angela M.; Barchowsky, Aaron; Bowser, Robert; Heiman-Patterson, Terry; Lacomis, David; Rana, Sandeep; Ada Youk; Talbott, Evelyn O.
Abstract: Background : Amyotrophic lateral sclerosis (ALS) is a serious and rapidly fatal neurodegenerative disorder with an annual incidence of 1–2.6/100, 000 persons. Few known risk factors exist although gene–environment interaction is suspected. We investigated the relationship between suspected neurotoxicant hazardous air pollutants (HAPs) exposure and ALS.Methods : A case–control study involving sporadic ALS cases ( n  = 51) and matched controls ( n  = 51) was conducted from 2008 to 2011. Geocoded residential addresses were linked to U.S. EPA NATA data (1999, 2002, and 2005) by census tract. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression.Results : Residential exposure to aromatic solvents significantly elevated the risk of ALS among cases compared to controls in 2002 (OR = 5.03, 95% CI: 1.29, 19.53) and 1999 (OR = 4.27, 95% CI: 1.09, 16.79) following adjustment for education, smoking, and other exposure groups. Metals, pesticides, and other HAPs were not associated with ALS.Conclusions : A potential relationship is suggested between residential ambient air aromatic solvent exposure and risk of ALS in this study. Highlights: The effects of ambient air pollutants and risk of ALS was assessed. EPA NATA data linked to geocoded addresses for 1999, 2002, and 2005. Residential exposure to aromatic solvents was associated with an increased risk of ALS. Abstract : Residential exposure to aromatic solvents was associated with an increased risk of ALS.